1234 IMPROVING HEART FAILURE MANAGEMENT WITHIN HOSPITAL AT HOME. (16th January 2023) - Ralston, K; Degnan, A; Groom, C; Leonard, C; Munang, L; Japp, A; Rimer, J
Abstract: Introduction: Heart failure (HF) is a common problem managed in our West Lothian multi-disciplinary hospital at home (HaH) service, however significant variation in practice was noted with considerable resource implications. We aimed to standardise and improve this by developing a dedicated protocol. Methods: We developed a protocol to guide the assessment and management of HF within HaH. We collected baseline (n=25) and follow-up data (n=10) after protocol introduction from patients referred to HaH with heart failure. Outcomes reviewed included anticipatory care planning (ACP) decisions, length of stay (LOS) and treatment strategy. We held staff education sessions and surveyed staff confidence regarding HF management. Results: ACP discussion rates improved after protocol introduction, with decision rates improving for both escalation of care (28% to 80%) and resuscitation (44% to 60%). LOS reduced after protocol introduction (mean 6.3 days to 5.9 days). Titration of oral diuretics alone (71%) was associated with a shorter LOS (mean 5.4 days) compared to IV (29%, mean 8.1 days), with no difference in 28 day outcome. In those with HF with reduced ejection fraction, the rates of beta-blocker prescription increased (57% to 80%) however ACE-inhibitor prescription decreased (29% to 20%). Use of add-on therapy (e.g. thiazide diuretics) increased (12% to 30%) with a decrease in complication rates (12% to 0%). All staff found the protocol helpful with an improvement in confidence levels. Conclusions: Through introducing a standardised protocol, we observed an improvement in anticipatory care discussion rates and a trend towards shorter LOS. Oral diuretic titration was less resource intensive without an adverse impact on outcome. Future plans include ongoing education and data collection, trialling a joint multi-disciplinary meeting with cardiology for discussion of complex patients and embedding a treatment strategy of oral diuretic titration with a 'discharge with planned review' approach in appropriate patients.